The Structure and Behavior of Cayenne Pepper Market - Ardhiles Oktama Timoranda Yusmadi Putra; Dewi Kurniati; Anita Suharyani (SOCA: Jurnal Sosial Ekonomi Pertanian, 2021)
The sale of cayenne pepper from farmers/producers to consumers required a marketing process. The long chain of cayenne pepper marketing and market structure leading to an unfair competition and price determination were dominated by the collectors. The research objective was to determine the marketing channels, market structure and market behavior of cayenne pepper in Sekadau Regency. The determination of the sample in this research was using a non-probability sampling method by using the Slovin formula. Data were analyzed using the Herfindahl Index (IH) and Minimum Economies of Scale (MES). The results showed that the cayenne pepper marketing channels that available in Sekadau Regency were 2 marketing channels. In general, the market structure of cayenne pepper lead to an oligopoly market, market behavior showed that the highest profit and income ratio was obtained by wholesalers. The price determination process was influenced by the large traders, the existence of price discrimination practices at each level of the marketing channel, and the establishment of binding cooperation between collectors and farmers. Farmers were advised to form institutions to strengthen their bargaining position in dealing with collector traders as price determinants and not always being price takers, as happened in the marketing channel 1. Local governments were expected to create an Agribusiness Sub Terminal (STA) which can help to open the market access.